Precipitation changes alter the structure, species composition and interspecific relationships of desert steppe plant communities - Kechen Song; Hao Zhang; Haiying Hu; Yingzhong Xie; Xiaona Zhao; Yiyin Zhang; Jiayi Yong; Wenhui Deng; Siyu Guan (Global Ecology and Conservation)
Precipitation (P) is the sole water source supporting plant growth in the desert steppe, governing the structure and function of plant communities. Nevertheless, how changes in precipitation alter species composition and affect interspecific relationships within plant communities remains unclear. To address this, we simulated five precipitation gradients, ranging from 50 % (P−50 %), 70 % (P−30 %), 100 % (PCK), 130 % (P+30 %), to 150 % (P+50 %) relative to ambient precipitation. We assessed the effects of precipitation treatments and seasonality on plant community structure and species composition in late spring, mid-summer, and late summer. Results showed that (1) The desert grassland plant community exhibited an asymmetric response to precipitation amount and seasonal variatt steppe ecosystems, interspecific connectivity reflecion, where the impact of late-spring precipitation on the quantitative traits, importance values (IV), and mean niche overlap of communities was greater than that of mid-summer and late-summer precipitation, and the effects of decreased precipitation were more significant than those of increased precipitation. (2) The niche of perennial plants did not change with the season, while the IV and ecological niche width (B) of annual plants increased as the seasons passed. (3) Decreased precipitation reduced the mean niche overlap of all species, the B of Leguminosae plants, and the IV of all species except for Stipa breviflora and Convolvulus ammannii. (4) The overall association index indicated a positive correlation among communities, showing significant correlations in P+50 %, P−30 %, and P−50 %. The association index between populations gradually shifted from negative to positive with decreasing precipitation. Therefore, we suggest that both drought and wetness tend to intensify interspecific interactions within the community. More importantly, drought transformed the population relationships from competition to mutualistic symbiosis.